Analysing Indispensability of Scaffolding Strategies to Enhance the Teaching of English Syntactical Structures to Grade 10 Learners - Farisani Thomas Nephawe; Munyadziwa Sylvia Nemakhavhani (English Department - University of Sultan Ageng Tirtayasa, 2024)
Although numerous research has been conducted on the versatility of the strategies for teaching the English language, studies on the indispensability of scaffolding strategies to enhance the teaching of English syntactical structures are limited. The present study analysed the indispensability of these strategies for improving the synthesis of English syntactical structures at a South African secondary school. A qualitative research approach was adopted to obtain an in-depth understanding of the indispensability of using scaffolding strategies in teaching synthesis of syntactical structures to Grade 10 English First Additional Language (EFAL) learners. The population of this study comprised seven teachers who had more than five years of teaching experience at the secondary school level. Five purposively sampled teachers participated in this study because the researchers did not want to have abnormal findings and discussions. The sample was a true representative of the entire population because learners taught were from the same rural communities and share similar characteristics such as limited exposure to the appropriate use of the English. language. Data were collected using classroom observations and semi-structured face-to-face interviews. Using thematic analysis, a preliminary investigation was conducted on three schoolteachers who were not part of the target respondents and were reluctant to use scaffolding strategies in the classroom. Nonetheless, after applying scaffolding strategies, the respondents performed profoundly. The implication of the present study necessitates the indispensability of scaffolding strategies. This study argues for the constant use of scaffolding strategies in synthesising English syntactical structures.